b - McFarlane, Penny (b, 2021)
"Dramatherapy offers a new and different way of providing support for children with emotional and behavioural problems. An easy-to-read guide for non-specialist teachers, this book explains the psychoanalytical method of intervention and gives clear guidance on how it works, with uncomplicated suggestions for helping pupils come to terms with particular issues and develop emotional stability. Written for teachers, SENCos, SEN support teachers, Educational Psychologists, Behaviour Support workers."--Jacket
Includes bibliographical references and index.
Keywords: Drama -- Therapeutic use; Drama in education -- Therapeutic use